Perancangan Generator Induksi 1 Fase 12 Kutub Kecepatan Rendah - khairudin, Nor rahman; , Agus Supardi, S.T., M.T; , Aris Budiman, S.T., M.T (2015)
Electrical energy is the energy that is essential to life in the country of Indonesia. The number of users resulting power deficit, because it is not offset by the addition of generating capacity. Moreover, Indonesia is a big country, with widely scattered islands. Then the energy distribution of electricity were still not sufficient hinterland. Small-scale power plants to be one alternative. Generator used is an induction generator among other types of multiple generators. Induction generator makes the mechanical energy is converted into electrical energy. Induction generator has a robust design, requiring no carbon brushes, easy maintenance, easy and operator of electricity may emit at different rotational speed. These characteristics make the induction generator to be one alternative small power plants in remote areas. This study about the induction generator 1 phase 12 pole low speed which dikopelkan with an induction motor as the driving and mounted switch controller capacitor bank, then testing the induction generator without load with the excitation capacitor 8 μF and 16 μF with a rotational speed between 525 rpm up to 850 rpm and with excitation 8μF capacitors and 16 μF at 525 putarantara speeds up to 850 rpm. After the test continued penggukuran output voltage, frequency and current, then the fetched data analyzed. Results of the research phase induction generator 1 low speed with capacitor banks 8 μF and 16 μF with a resistive load of 5.10 and 15 Watt. Characteristics of the rotational speed of the V and F when the load increases, namely V and f is decreasing because the generator rotation slowed. Without load capacitor 8 μF speed of 605 rpm is 122 V, 57.5 Hz, with a load of 117 V, 57.5 Hz. Without load 16 μF speed of 605 rpm is 119V, 56.7 Hz, with a load of 117 V, 57.5 Hz, the voltage is reduced to 4.2%. causes the voltage and frequency on the wane as a result of the rotary keceptan increasingly slowing down and also the effect of the increased load makes the generator rotating heavy. To overcome the voltage drop by adding a rotational speed of the generator so that the load can be met.